Protocol for a Randomised controlled trial to Evaluate the effectiveness and cost benefit of prescribing high dose FLuoride toothpaste in preventing and treating dEntal Caries in high-risk older adulTs (reflect trial) - Tickle, M. (BMC Oral Health, 2019)
BACKGROUND: Dental caries in the expanding elderly, predominantly-dentate population is an emerging public health concern. Elderly individuals with heavily restored dentitions represent a clinical challenge and significant financial burden for healthcare systems, especially when their physical and cognitive abilities are in decline. Prescription of higher concentration fluoride toothpaste to prevent caries in older populations is expanding in the UK, significantly increasing costs for the National Health Services (NHS) but the effectiveness and cost benefit of this intervention are uncertain. The Reflect trial will evaluate the effectiveness and cost benefit of General Dental Practitioner (GDP) prescribing of 5000 ppm fluoride toothpaste and usual care compared to usual care alone in individuals 50 years and over with high-risk of caries. METHODS/DESIGN: A pragmatic, open-label, randomised controlled trial involving adults aged 50 years and above attending NHS dental practices identified by their dentist as having high risk of dental caries. Participants will be randomised to prescription of 5000 ppm fluoride toothpaste (frequency, amount and duration decided by GDP) and usual care only. 1200 participants will be recruited from approximately 60 dental practices in England, Scotland and Northern Ireland and followed up for 3 years. The primary outcome will be the proportion of participants receiving any dental treatment due to caries. Secondary outcomes will include coronal and root caries increments measured by independent, blinded examiners, patient reported quality of life measures, and economic outcomes; NHS and patient perspective costs, willingness to pay, net benefit (analysed over the trial follow-up period and modelled lifetime horizon). A parallel qualitative study will investigate GDPs’ practises of and beliefs about prescribing the toothpaste and patients’ beliefs and experiences of the toothpaste and perceived impacts on their oral health-related behaviours. DISCUSSION: The Reflect trial will provide valuable information to patients, policy makers and clinicians on the costs and benefits of an expensive, but evidence-deficient caries prevention intervention delivered to older adults in general dental practice. TRIAL REGISTRATION: ISRCTN: 2017-002402-13 registered 02/06/2017, first participant recruited 03/05/2018. Ethics Reference No: 17/NE/0329/233335. Funding Body: Health Technology Assessment funding stream of National Institute for Health Research. Funder number: HTA project 16/23/01. Trial Sponsor: Manchester University NHS Foundation Trust, Oxford Road, Manchester, M13 9WL. The Trial was prospectively registered. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12903-019-0749-x) contains supplementary material, which is available to authorized users.